Professional translational research: a new hybrid paradigm in early drug discovery. (September 2015) - Nussbaumer, Peter; Klebl, Bert
While industry makes cuts to early drug discovery research, the demand for innovation in the pursuit of novel medicines continues to grow. Who should fill this gap? Academia clearly is a rich source of innovation but how can new basic research concepts find their way into industrial application? A new paradigm for early drug discovery involves professional translational research centers, which function as facilitators and translators at the academia–industry interface, harnessing the strengths of both worlds and leveraging the high innovation potential of academia by using the robustness and efficiency of industry. In this article, the authors discuss the set-up and essential requirements for the successful translation of new drug concepts.